Principles and practice of antibiotic stewardship in the management of diabetic foot infections. Issue 2 (April 2019) - Uçkay, Ilker; Berli, Martin; Sendi, Parham; Lipsky, Benjamin A.
Abstract : Purpose of review: Systemic antibiotic therapy in persons with a diabetic foot infection (DFI) is frequent, increasing the risk of promoting resistance to common pathogens. Applying principles of antibiotic stewardship may help avoid this problem. Recent findings: We performed a systematic review of the literature, especially seeking recently published studies, for data on the role and value of antibiotic stewardship (especially reducing the spectrum and duration of antibiotic therapy) in community and hospital populations of persons with a DFI. Summary: We found very few publications specifically concerning antibiotic stewardship in persons with a DFI. The case-mix of these patients is substantial and infection plays only one part among several chronic problems. As with other types of infections, attempting to prevent infections and avoiding or reducing the spectrum and duration of antibiotic therapy are perhaps the best ways to reduce antibiotic prescribing in the DFI population. The field is complex and necessitates knowledge over the current scientific literature and clinical experience. On a larger scale, clinical pathways, guidelines, and recommendations are additionally supportive.